Vaccination coverage and its determinants in patients with multiple sclerosis—a multicenter cross-sectional study - Paula Schade; Hai-Anh Nguyen; Julia Steinle; Kerstin Hellwig; Teodor Pelea; Philipp Franken; Birte Elias-Hamp; Veit Becker; Stefan Merkelbach; Stephan Richter; Bert Wagner; Christian Geis; et al. (Therapeutic Advances in Neurological Disorders)
Background: Complete vaccination coverage is recommended by multiple sclerosis (MS) societies for patients with multiple sclerosis (pwMS) to mitigate infection risks associated with disease-modifying therapies (DMTs). Objectives: To analyze vaccination coverage and its determinants in pwMS compared to healthy controls, considering vaccination hesitancy, MS-specific vaccination beliefs, trust in information sources, and the role of general practitioners (GPs). Methods: This cross-sectional multicenter observational study was conducted in six German MS centers. The primary endpoint was a vaccination index (VI) comprising eight standard vaccinations (range 0–1, with higher VI indicating better vaccination coverage). Secondary endpoints included validated measures of general vaccination hesitancy, MS-specific vaccination beliefs, and trust in information sources. Data were collected through questionnaires, vaccination card analysis, and a survey of GPs who vaccinate pwMS. Results: VI tended to be lower in pwMS ( n  = 397) compared to healthy controls ( n  = 300; 0.58 ± 0.30 vs 0.62 ± 0.31, p  = 0.057). In pwMS receiving highly effective DMTs, VI did not differ significantly from those on no/platform DMTs. Vaccination hesitancy was comparably low, with no differences between pwMS and controls. Vaccination hesitancy, beliefs, and trust in information sources explained only 10%–16% of the variance in VI. Among 109 GPs, 82% cited reluctance to vaccinate pwMS due to concerns about MS-related side effects or interactions with DMTs. Conclusion: Despite clear recommendations from MS societies for full vaccination of all pwMS, vaccination coverage remains worryingly low. Approximately half of the patients lack standard vaccination coverage, even those on highly effective DMTs. In fact, vaccination coverage in pwMS tended to be even lower than in healthy controls. Vaccination hesitancy and other intrinsic factors do not sufficiently explain the low vaccination rates. Inconsistent vaccination recommendations from GPs due to uncertainties about vaccine safety and DMT interactions likely contribute.